TransOrbital NeuroEndoscopic Surgery for Biopsy of the Left Cavernous Sinus: A Literature Review, Case Report, and Cadaveric Proof of Concept - Frontera, Natasha L.; Rosado-Philippi, Julio; Díaz, Francisco Del Valle; Díaz, Alejandra Santiago; Medina, Adriana Vázquez; Figueroa, Arnaldo; González, Natalia; Pradilla, Gustavo; Garzón, Tomas; Rodríguez, Julio; Tarrats, Luisam; Valle, Miguel Mayol del (Journal of Neurological Surgery Reports, 2023)
The aim of this report is to describe TransOrbital NeuroEndoscopic Surgery (TONES) as a safe alternative for obtaining a cavernous sinus (CS) biopsy. We describe this technique in a patient with a diffuse large B cell lymphoma mimicking Tolosa–Hunt's syndrome. Articles were gathered querying PubMed, Embase, and Scopus databases with terms related to a “transorbital neuroendoscopic approach.” The literature search was performed by two independent authors (N.L.F. and J.R.), with inconsistencies resolved by the senior author (M.M.D.V.). After screening abstracts for relevance, full-length articles were reviewed for pertinent variables. A comparison was conducted with the illustrative case of a 69-year-old woman who presented to the emergency department with vertigo, ophthalmoplegia, and diplopia for 2 months. A brain magnetic resonance imaging revealed an infiltrative lesion at the left CS. A presumptive diagnosis of Tolosa–Hunt syndrome was made, but a confirmatory biopsy was performed using TONES. Based on our cadaveric study, literature review, and case report, the TONES approach was safe, effective for tissue diagnosis, and associated with minor morbidity and reduced hospital stay. Additional prospective studies are required to study its viability and safety in a larger group of patients.
Keywords: TransOrbital NeuroEndoscopic Surgery; cavernous sinus; biopsy; lymphoma; systematic review